An Occupational Therapy and Teaching Partnership: Applying a Scholarship of Practice Model. Issue 3 (3rd July 2017) - Fitzgerald, Brian; MacCobb, Siobhán
ABSTRACT: Occupational therapists must generate knowledge and evidence that relates specifically to their practice context especially when there is a paucity of literature for emerging areas of practice. This paper describes the process of adopting a scholarship of practice approach with other professionals to generate evidence for practice in mainstream post primary school settings with students with social, emotional and behavioral difficulties (SEBD). Scholarship of practice and clinical reasoning are closely intertwined as therapists generate evidence on their practice to make informed decisions and judgments. In this paper, there are a number of important concepts needing to be highlighted for their meaning in this specific context.